Partial Perception and Approximate Understanding - Lewandowska-Tomaszczyk, Barbara (Research in Language, 2017)
What is discussed in the present paper is the assumption concerning a human narrowed sense of perception of external world and, resulting from this, a basically approximate nature of concepts that are to portray it. Apart from the perceptual vagueness, other types of vagueness are also discussed, involving both the nature of things, indeterminacy of linguistic expressions and psycho-sociological conditioning of discourse actions in one language and in translational contexts. The second part of the paper discusses the concept of conceptual and linguistic resemblance (similarity, equivalence) and discourse approximating strategies and proposes a Resemblance Matrix, presenting ways used to narrow the approximation gap between the interacting parties in monolingual and translational discourses.